Graphene coated aluminum silver powder coating and preparation method and use method thereof
Through the technical means of graphene-coated aluminum-silver powder, the contradiction between thermal conductivity and corrosion resistance of traditional coatings is solved, the high weather resistance and good heat dissipation performance of the coating is achieved, and the protective effect of the coating is significantly improved.
Patent Information
- Application Number
- CN202411785073.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
There is a contradiction between thermal conductivity and corrosion resistance of traditional coatings. In the prior art, aluminum silver paste and graphene are simply mixed with mechanically, resulting in insufficient weather resistance and heat dissipation performance of the coating.
Graphene is coated with aluminum silver powder, and aluminum-hydrogen bonds are generated through ultrasonic dispersion and acid-base reaction. Graphene oxide is reduced in situ to graphene to form a uniform and tight conductive network, which enhances the electrochemical protection and heat dissipation effect of the coating.
It significantly improves the weather resistance and heat dissipation performance of the paint, enhances the protection and operability of the workpiece, and extends the recoating time of the paint.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to graphene-coated aluminum silver powder, a preparation method thereof and application thereof in coatings. Background Art
[0002] Anti-corrosion coatings are extremely important in industrial applications, but traditional coatings have a contradiction between thermal conductivity and corrosion resistance. To solve this problem, graphene has become an ideal choice for improving coating performance due to its unique physical and chemical properties. Graphene has excellent adhesion, water resistance, hardness and stability, and can remain stable in high temperature and corrosive environments.
[0003] The Chinese invention patent application with publication number CN109233565A and publication date January 18, 2019 proposes a heavy-duty anti-corrosion graphene-modified epoxy zinc-rich coating and a method for making the same. The heavy-duty anti-corrosion graphene-modified epoxy zinc-rich coating is made of the following raw materials in weight percentage: epoxy resin 18~25wt%, anti-settling agent 1.5~3wt%, organic solvent 12~16wt%, coated aluminum silver paste 1~3wt%, functional filler 10~25wt%, nano-graphene additive 0.1~0.5wt%, functional additive 0.2~0.5wt%, modified fatty amine curing agent 12~16wt%, and the rest is zinc powder.
[0004] The strong physical shielding layer formed by the coated aluminum-silver paste and the two-dimensional flake structure of graphene has substantially improved the weather resistance performance, which can delay the powdering of the epoxy coating, thereby extending the recoating time of the matching coating and making the coating more operable and constructible.
[0005] Regarding the above technical solutions, although this type of material improves the weather resistance of the coating, the aluminum-silver paste and graphene are simply mechanically mixed. Adding them together can only bring out the characteristics of both of them, which is insufficient to improve the weather resistance and strength of the coating, and also does not improve the heat dissipation performance of the material. Summary of the invention
[0006] In order to further improve the weather resistance and heat dissipation performance of the coating, the present invention provides a graphene-coated aluminum silver powder, a preparation method thereof, and an application thereof in the coating.
[0007] In the first aspect, the present invention provides a graphene-coated aluminum silver powder coating, which adopts the following technical solution: A graphene-coated aluminum silver powder coating comprises the following components and their weight proportions: Component A: 26-33 epoxy resin, 13-17 xylene, 13-17 n-butanol, 13-17 organic-inorganic double-coated aluminum-silver paste, 4-6 sericite, 17-22 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, 0.05 defoaming agent, the aluminum-silver paste of the organic-inorganic double-coated aluminum-silver paste is graphene-coated aluminum-silver paste, the graphene-coated aluminum-silver paste includes graphene-coated aluminum-silver powder, the leveling agent is a polyether-modified silicone leveling agent, and the defoaming agent is a polyether-modified silicone defoaming agent; Component B: 50 hexahydrophthalic anhydride, 2 anhydride accelerator, 24 xylene, 24 n-butanol.
[0008] By adopting the above technical solution, graphene has a very high electron mobility, can conduct electrons quickly, and can form a conductive network in the coating. When the aluminum silver powder conductive particles in the coating are oxidized and the conductivity decreases, graphene can act as a conductive bridge to maintain the electrochemical protection of the coating. Graphene has very good thermal conductivity. The addition of graphene can improve the heat dissipation effect. Graphene has high chemical stability and is not easily corroded by corrosive media, thereby maintaining the anti-corrosion performance of the coating for a long time; graphene has strong hydrophobicity and can form a water-proof layer on the surface of the coating to prevent water molecules in the air from entering the surface of the workpiece, thereby enhancing the protection of the workpiece.
[0009] Aluminum silver powder can reflect ultraviolet rays, infrared rays, and visible light, and has a heat dissipation effect on sunlight. At the same time, aluminum silver powder is corrosion-resistant and reacts with oxygen to form a dense aluminum oxide film that can protect aluminum from further oxidation.
[0010] However, aluminum powder easily reacts with water, oxygen, etc., which reduces or loses its excellent performance. The surface coating modification of aluminum powder is of great significance to improving its stability in corrosive media. The coated aluminum-silver paste has better acid and alkali resistance and UV resistance than the uncoated aluminum-silver paste.
[0011] Optionally, the epoxy resin is an alicyclic epoxy resin.
[0012] By adopting the above technical solution, the alicyclic epoxy resin can form a tight rigid molecular structure because the epoxy group is directly connected to the alicyclic ring, and the cross-linking density is large after curing, so the heat deformation temperature is high. Unlike ordinary bisphenol A epoxy resin, the alicyclic epoxy resin does not contain a benzene ring in its molecular structure, so it has good weather resistance and ultraviolet radiation resistance. At the same time, the reaction activity of the alicyclic epoxy resin to acid anhydride is greater than that to amines, and it can be fully cured in the acid anhydride system, which can avoid the use of amine curing agents with high toxicity and volatility, and is safer for operators.
[0013] In a second aspect, the present invention provides a method for preparing a graphene-coated aluminum silver powder coating, which adopts the following technical solution: A method for preparing a graphene-coated aluminum silver powder coating comprises the following steps: S1. Preparation of graphene-coated aluminum silver powder: S11, adding graphene oxide powder to deionized water, wherein the graphene oxide flake thickness is 1-10 nanometers and the diameter is 1-10 μm, and ultrasonic dispersion is performed for 30-120 minutes at an ultrasonic frequency of 50-100 KHz to obtain a graphene oxide dispersion liquid, wherein the concentration range of the graphene oxide dispersion liquid is 1-100 g / L; S12, adding aluminum silver powder to the graphene oxide dispersion, wherein the particle size of the aluminum silver powder is in the range of 1 to 100 μm, and the mass ratio of graphene oxide to the aluminum silver powder in the graphene oxide dispersion is 1: (100 to 1000); S13, using sulfuric acid or hydrochloric acid to adjust the pH of the graphene oxide dispersion, reacting at room temperature, using a stirring device to continuously stir during the reaction, the stirring speed range is 10-60r / min, and the pH range is 1-6; S14. After the reaction is completed, the obtained product is washed, filtered, and dried in an oven until completely dry to obtain graphene-coated aluminum silver powder.
[0014] S2. Preparation of graphene-coated aluminum-silver paste: S21, taking 100 parts of the graphene-coated aluminum silver powder, 100 parts of D80 solvent oil, and 1 part of fatty acid, adding them into a ball mill and mixing and grinding for 5 hours to obtain a mixed slurry; S22, adding the mixed slurry to a vibrating screen with a mesh size of 250 meshes for filtering, and then adding the filtered mixed slurry to a filter press for pressing to obtain a graphene-coated aluminum-silver paste filter cake; S23, adding the graphene-coated aluminum-silver paste filter cake into a mixer and stirring evenly to obtain the graphene-coated aluminum-silver paste.
[0015] S3, preparation of organic-inorganic double-coated aluminum-silver paste: S31, dispersing: dispersing the graphene-coated aluminum-silver paste in a mixed solvent of ethanol and water to obtain a uniform precursor; the volume ratio of the ethanol and water is 1:1, and the amount of the mixed solvent of ethanol and water added is 350% of the weight of the aluminum-silver paste; S32, inorganic coating: the above precursor is dripped into tetraethyl orthosilicate within 1 hour, and the mixture is stirred and heated while the temperature of the whole system is controlled at 60-70°C, and a hydrolysis reaction is carried out under the catalytic action of ammonia water. After completion, the mixture is cooled, washed and filtered to obtain an inorganic silica-coated / graphene-coated aluminum-silver paste; tetraethyl orthosilicate is used as a precursor of silica, and its addition amount is 40% of the weight of the aluminum-silver paste; the addition amount of ammonia water is 10% of the weight of the aluminum-silver paste; S33, organic coating: add toluene to a round-bottom flask equipped with a stirrer, a dropping funnel, and a reflux condenser, and disperse the inorganic silica-coated aluminum paste in toluene, wherein the amount of toluene added is 350% of the weight of the aluminum paste; then stir thoroughly for 30 minutes, and add silane coupling agent and azobisisobutyronitrile in sequence, wherein the amount of silane coupling agent added is 2% of the weight of the inorganic silica-coated aluminum paste, and the amount of azobisisobutyronitrile added is 1% of the weight of the inorganic silica-coated aluminum paste. 2%, evacuate the system and pass inert gas, repeat three times, and keep the whole reaction process under the protection of continuous inert gas atmosphere, place the round-bottom flask in a water bath and heat it to 70°C, and then add fluorine-containing acrylate monomer dropwise, wherein the addition amount of the fluorine-containing acrylate monomer is 50% of the weight of the inorganic silica-coated aluminum-silver paste; the addition is completed in 1 hour; the system temperature is raised to 85°C and the reaction is continued for 4 hours, cooled, washed and filtered to obtain the organic-inorganic double-coated aluminum-silver paste.
[0016] S4. Preparation of super weather-resistant graphene anti-corrosion heat dissipation coating: Preparation method of component A: Add xylene and n-butanol into a stirring tank, turn on the high-speed disperser at a speed of 500-700 r / min for 1-10 min to obtain a uniformly mixed solvent; After adding alicyclic epoxy resin to the uniformly mixed solvent, the rotation speed is adjusted to 1500-2000 r / min, and the mixture is heated at 50-100° C. until the alicyclic epoxy resin is completely dissolved to obtain a mixture A; Add organic-inorganic double-coated aluminum silver paste, sericite, aluminum tripolyphosphate and fumed silica to mixture A, disperse at 1500-2000 r / min for 2-3 hours, and measure the fineness with a scraper fineness meter to be less than 20 μm, to obtain mixture B; Adjust the speed to 800~1000r / min, add the leveling agent and defoaming agent into mixture B, stir for 10~15min, filter with 200-mesh filter cloth, and package.
[0017] Preparation method of component B: Add xylene, n-butanol, hexahydrophthalic anhydride and acid anhydride promoter into a stirring tank at a stirring speed of 800-1000 r / min. After the hexahydrophthalic anhydride and acid anhydride promoter are completely dissolved, filter with a 300-mesh filter and package.
[0018] By adopting the above technical solution, aluminum-silver powder reacts with sulfuric acid or hydrochloric acid to generate aluminum-hydrogen bonds, which have strong reducing ability, and can reduce graphene oxide to graphene in situ on the aluminum-silver surface.
[0019] Al+H + →Al 3+ +H2→Al 3+ +2·H→Al-H (aluminum-hydrogen bond) Al-H + GO (graphene oxide) → Al-RGO (graphene oxide is in situ reduced to graphene on the aluminum-silver surface) + H Compared with the simple mechanical stirring and mixing of graphene directly added to the coating system, the method of graphene coating aluminum silver makes the graphene evenly distributed and the graphene and aluminum silver are firmly combined. In this way, the graphene and aluminum silver can form a uniform and tight conductive network in the coating, enhancing the electrochemical protection of the coating and thus improving the anti-corrosion performance.
[0020] At the same time, hexahydrophthalic anhydride is used as a curing agent for epoxy resin. If the AB components are not separated, the coating will be cured before use. After the AB components are separated, they can be mixed according to the proportion and used immediately, and then cured on the surface of the workpiece after spraying.
[0021] Optionally, the mass ratio of graphene oxide to aluminum silver powder in the graphene oxide dispersion in S12 is 1:(500~800).
[0022] By adopting the above technical solution, within this range, aluminum silver is basically coated with graphene, and at the same time, there will be no excessive situation of either aluminum silver or graphene; below this range, there is less aluminum silver and more graphene, and the aluminum silver is basically coated, but there will be more remaining graphene; above this range, there is more aluminum silver and less graphene, and some aluminum silver will not be coated.
[0023] Optionally, the pH range of S13 is 1~4.
[0024] By adopting the above technical solution, the lower the pH, the higher the hydrogen ion content, the more aluminum-hydrogen bonds are generated, and thus the rate of reducing graphene oxide is faster and more complete.
[0025] In a third aspect, the present invention provides a method for using a graphene-coated aluminum silver powder coating, which adopts the following technical solution: A method for using a graphene-coated aluminum silver powder coating comprises the following steps: Pretreatment: Pre-treat the metal surface by sandblasting, degreasing and rust removal, water washing, phosphating, passivation, deionized water washing, and drying of the phosphating film to remove oil and dust on the surface of the coated object; Spraying: Mix component A and component B in a ratio of 1:0.5 and spray on the workpiece; Curing: After spraying, let the workpiece dry in a 30℃ environment for 10-20 minutes, then cure the workpiece at 120-150℃ for 1 hour, and polish with 240-grit sandpaper.
[0026] By adopting the above technical solution, graphene-coated aluminum silver powder coating can be sprayed onto the metal surface.
[0027] Optionally, a secondary spraying and curing step is added after the curing step. Secondary spraying and curing: Follow the same spraying and curing steps as above to carry out secondary spraying and curing.
[0028] By adopting the above technical solution, since a thick spray coating will cause sagging, poor defoaming, and the bottom solvent is not easy to volatilize, there will be more defects on the coating surface. The second spray coating can cover the coating defects, so the two-coating process is adopted, and the dry film thickness reaches 80~100μm. In summary, the present invention includes at least one of the following beneficial technical effects: 1. The heat dissipation and anti-corrosion coating of the present invention can not only dissipate heat, but also has anti-corrosion effect, and is very suitable for use in fields requiring heat dissipation in the ocean.
[0029] 2. The present invention has excellent corrosion resistance by using alicyclic epoxy resin with good resistance to ultraviolet rays, acid and alkali, and the anti-corrosion performance of graphene is combined. The combination of the two has a synergistic effect, amplifies the corrosion resistance, and has excellent corrosion resistance. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below with reference to the embodiments.
[0031] In a specific embodiment of the present invention, the reagents and instruments used in the following examples can all be purchased as commercial products.
[0032] The polymer epoxy resin is multifunctional alicyclic epoxy resin EPHE3150 produced by Daicel Japan.
[0033] Xylene was obtained from Sinopharm Chemical Reagent Co., Ltd., ≥99.0%.
[0034] The n-butanol was from Sinopharm Chemical Reagent Co., Ltd., with a content of ≥99.0%.
[0035] The sericite mica is GA-6 produced by Anhui Ge Rui New Material Technology Co., Ltd., with an average particle size of 15±1.5μm, an oil absorption value of 35~42g / 100g, and a pH value of 4~7.
[0036] The aluminum tripolyphosphate is aluminum tripolyphosphate APW-1 produced by Changzhou Aked New Material Technology Co., Ltd., and the oil absorption value is 35~45g / 100g.
[0037] Evonik Degussa AEROSIL ® 200 is a hydrophilic fumed silica with a BET surface area of 175~225m² / g, suitable for a variety of applications.
[0038] The leveling agent is BYK-333 silicone leveling agent and TEGO-450 silicone leveling agent.
[0039] The defoaming agent is BYK-077 silicone defoaming agent produced by BYK Chemical and TEGO Foamex N silicone defoaming agent produced by TEGO.
[0040] Hexahydrophthalic anhydride is from Sinopharm Chemical Reagent Co., Ltd., ≥99.0% hexahydrophthalic anhydride.
[0041] The anhydride accelerator is the non-yellowing anhydride accelerator H-600 produced by Chuzhou Huisheng Electronic Materials Co., Ltd.
[0042] Embodiment 1: This embodiment discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: alicyclic epoxy resin 28.11, xylene 14.05, n-butanol 14.05, organic and inorganic double coated aluminum silver paste 14.55, sericite 4.68, aluminum tripolyphosphate 18.74, fumed silica 1, leveling agent 0.1, defoamer 0.05, Component B: 50 hexahydrophthalic anhydride, 2 anhydride accelerator, 24 xylene, 24 n-butanol.
[0043] The preparation method is as follows, S1. Preparation of graphene-coated aluminum silver powder: S11, adding graphene oxide powder to deionized water, and ultrasonically dispersing for 60 minutes at an ultrasonic frequency of 80 KHz to obtain a graphene oxide dispersion, wherein the graphene oxide sheet has a thickness of 1 to 10 nanometers and a diameter of 1 to 10 μm, and the concentration of the graphene oxide dispersion is 50 g / L; S12, adding aluminum silver powder to the graphene oxide dispersion, wherein the particle size of the aluminum silver powder is in the range of 1 to 100 μm, and the mass ratio of graphene oxide to the aluminum silver powder in the graphene oxide dispersion is 1:650; S13, using sulfuric acid or hydrochloric acid to adjust the pH of the graphene oxide dispersion, reacting at room temperature, using a stirring device to continuously stir during the reaction, the stirring speed range is 30r / min, and the pH is 1; S14. After the reaction is completed, the obtained product is washed, filtered, and dried in an oven until completely dry to obtain graphene-coated aluminum silver powder.
[0044] S2. Preparation of graphene-coated aluminum-silver paste: S21, taking 100 parts of the graphene-coated aluminum silver powder, 100 parts of D80 solvent oil, and 1 part of fatty acid, adding them into a ball mill and mixing and grinding for 5 hours to obtain a mixed slurry; S22, adding the mixed slurry to a vibrating screen with a mesh size of 250 meshes for filtering, and then adding the filtered mixed slurry to a filter press for pressing to obtain a graphene-coated aluminum-silver paste filter cake; S23, adding the graphene-coated aluminum-silver paste filter cake into a mixer and stirring evenly to obtain the graphene-coated aluminum-silver paste.
[0045] S3, preparation of organic-inorganic double-coated aluminum-silver paste: S31, dispersing: dispersing the graphene-coated aluminum-silver paste in a mixed solvent of ethanol and water to obtain a uniform precursor; the volume ratio of the ethanol and water is 1:1, and the amount of the mixed solvent of ethanol and water added is 350% of the weight of the aluminum-silver paste; S32, inorganic coating: the above precursor is dripped into tetraethyl orthosilicate within 1 hour, and the mixture is stirred and heated while the temperature of the whole system is controlled at 60-70°C, and a hydrolysis reaction is carried out under the catalytic action of ammonia water. After completion, the mixture is cooled, washed and filtered to obtain an inorganic silica-coated / graphene-coated aluminum-silver paste; tetraethyl orthosilicate is used as a precursor of silica, and its addition amount is 40% of the weight of the aluminum-silver paste; the addition amount of ammonia water is 10% of the weight of the aluminum-silver paste; S33, organic coating: add toluene to a round-bottom flask equipped with a stirrer, a dropping funnel, and a reflux condenser, and disperse the inorganic silica-coated aluminum paste in toluene, wherein the amount of toluene added is 350% of the weight of the aluminum paste; then stir thoroughly for 30 minutes, and add silane coupling agent and azobisisobutyronitrile in sequence, wherein the amount of silane coupling agent added is 2% of the weight of the inorganic silica-coated aluminum paste, and the amount of azobisisobutyronitrile added is 1% of the weight of the inorganic silica-coated aluminum paste. 2%, evacuate the system and pass inert gas, repeat three times, and keep the whole reaction process under the protection of continuous inert gas atmosphere, place the round-bottom flask in a water bath and heat it to 70°C, and then add fluorine-containing acrylate monomer dropwise, wherein the addition amount of the fluorine-containing acrylate monomer is 50% of the weight of the inorganic silica-coated aluminum-silver paste; the addition is completed in 1 hour; the system temperature is raised to 85°C and the reaction is continued for 4 hours, cooled, washed and filtered to obtain the organic-inorganic double-coated aluminum-silver paste.
[0046] S4. Preparation of super weather-resistant graphene anti-corrosion heat dissipation coating: Preparation method of component A: Add xylene and n-butanol into a stirring tank, turn on the high-speed disperser at a speed of 600 r / min for 5 min to obtain a uniformly mixed solvent; After adding alicyclic epoxy resin to the uniformly mixed solvent, the rotation speed is adjusted to 1600 r / min, and the mixture is heated at 80° C. until the alicyclic epoxy resin is completely dissolved, thereby obtaining a mixture A; Add organic-inorganic double-coated aluminum silver paste, sericite, aluminum tripolyphosphate and fumed silica to mixture A, disperse at 1600 r / min for 2.5 hours, and measure the fineness with a scraper fineness meter to be less than 20 μm, to obtain mixture B; Adjust the speed to 800r / min, add the leveling agent and defoamer to mixture B, stir for 15min, filter with 200-mesh filter cloth, and package.
[0047] Preparation method of component B: Add xylene, n-butanol, hexahydrophthalic anhydride and acid anhydride promoter into a stirring tank at a stirring speed of 900 r / min. After the hexahydrophthalic anhydride and acid anhydride promoter are completely dissolved, filter with a 300-mesh filter and package.
[0048] The usage is as follows: Pretreatment: Pre-treat the metal surface by sandblasting, degreasing and rust removal, water washing, phosphating, passivation, deionized water washing, and drying of the phosphating film to remove oil and dust on the surface of the coated object; Spraying: Mix component A and component B in a ratio of 1:0.5 and spray on the workpiece; Curing: After spraying, let the workpiece dry in a 30℃ environment for 10-20 minutes, then cure the workpiece at 120-150℃ for 1 hour, and polish with 240-grit sandpaper.
[0049] Secondary spraying and curing: Follow the same spraying and curing steps as above to carry out secondary spraying and curing.
[0050] Embodiment 2: This embodiment discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: 26.15 alicyclic epoxy resin, 13.86 xylene, 13.86 n-butanol, 13.00 organic-inorganic double-coated aluminum silver paste, 4.62 sericite, 17.48 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, and 0.05 defoaming agent.
[0051] The rest is exactly the same as in Example 1.
[0052] Embodiment 3: This embodiment discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: 32.62% alicyclic epoxy resin, 16.75% xylene, 16.75% n-butanol, 17.00% organic-inorganic double-coated aluminum silver paste, 5.16% sericite, 21.26% aluminum tripolyphosphate, 1% fumed silica, 0.1% leveling agent, and 0.05% defoaming agent.
[0053] The rest is exactly the same as in Example 1.
[0054] Embodiment 4: This embodiment discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: 28.11 alicyclic epoxy resin, 14.05 xylene, 14.05 n-butanol, 14.55 organic-inorganic double-coated aluminum silver paste, 4.68 sericite, 18.74 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, and 0.05 defoaming agent.
[0055] The preparation method is as follows, S12. The mass ratio of graphene oxide to aluminum silver powder in the graphene oxide dispersion is 1:100.
[0056] The rest is exactly the same as in Example 1.
[0057] Embodiment 5: This embodiment discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: 28.11 alicyclic epoxy resin, 14.05 xylene, 14.05 n-butanol, 14.55 organic-inorganic double-coated aluminum silver paste, 4.68 sericite, 18.74 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, and 0.05 defoaming agent.
[0058] The preparation method is as follows, S12. The mass ratio of graphene oxide to aluminum silver powder in the graphene oxide dispersion is 1:1000.
[0059] The rest is exactly the same as in Example 1.
[0060] Embodiment 6: This embodiment discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: 28.11 alicyclic epoxy resin, 14.05 xylene, 14.05 n-butanol, 14.55 organic-inorganic double-coated aluminum silver paste, 4.68 sericite, 18.74 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, and 0.05 defoaming agent.
[0061] The preparation method is as follows, S13. The pH range is 6.
[0062] The rest is exactly the same as in Example 1.
[0063] Comparative Example 1: This comparative example discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: 28.11 alicyclic epoxy resin, 14.05 xylene, 14.05 n-butanol, 4.68 sericite, 18.74 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, and 0.05 defoaming agent.
[0064] Preparation method of component A: Add xylene and n-butanol into a stirring tank, turn on the high-speed disperser at a speed of 600 r / min for 5 min to obtain a uniformly mixed solvent; After adding alicyclic epoxy resin into the uniformly mixed solvent, the rotation speed is adjusted to 1600 r / min, and the mixture is heated at 80° C. until the alicyclic epoxy resin is completely dissolved, thereby obtaining a mixture A; Add sericite, aluminum tripolyphosphate and fumed silica to mixture A, disperse at 1600 r / min for 2.5 hours, and measure the fineness with a scraper fineness meter to be less than 20 μm, to obtain mixture B; Adjust the speed to 800r / min, add the leveling agent and defoamer to mixture B, stir for 15min, filter with 200-mesh filter cloth, and package.
[0065] The preparation method and application of component B are exactly the same as those in Example 1.
[0066] Comparative Example 2: This comparative example discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Bisphenol A epoxy resin E20 28.11, xylene 14.05, n-butanol 14.05, organic-inorganic double-coated aluminum silver paste 14.55, sericite 4.68, aluminum tripolyphosphate 18.74, fumed silica 1, leveling agent 0.1, defoaming agent 0.05.
[0067] Preparation method of component A: (2) After adding bisphenol A epoxy resin E20 to the uniformly mixed solvent, adjust the speed to 1600 r / min and heat at 80° C. until the bisphenol A epoxy resin E20 is completely dissolved to obtain mixture A.
[0068] The rest is exactly the same as in Example 1.
[0069] Comparative Example 3: This comparative example discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: alicyclic epoxy resin 26.00, xylene 13.00, n-butanol 13.00, organic-inorganic double-coated aluminum silver paste 5.00, sericite 4.00, aluminum tripolyphosphate 17.00, fumed silica 1, leveling agent 0.1, defoaming agent 0.05.
[0070] The rest is exactly the same as in Example 1.
[0071] Comparative Example 4: This comparative example discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: alicyclic epoxy resin 33.00, xylene 17.00, n-butanol 17.00, organic-inorganic double-coated aluminum silver paste 30.00, sericite 6.00, aluminum tripolyphosphate 22.00, fumed silica 1, leveling agent 0.1, defoaming agent 0.05.
[0072] The rest is exactly the same as in Example 1.
[0073] Comparative Example 5: This comparative example discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: 28.11 alicyclic epoxy resin, 14.05 xylene, 14.05 n-butanol, 14.55 organic-inorganic double-coated aluminum silver paste, 4.68 sericite, 18.74 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, and 0.05 defoaming agent.
[0074] The preparation method is as follows, S12. The mass ratio of graphene oxide to aluminum silver powder in the graphene oxide dispersion is 1:50.
[0075] The rest is exactly the same as in Example 1.
[0076] Comparative Example 6: This comparative example discloses a super weather-resistant graphene anti-corrosion heat dissipation coating, comprising the following components and their weight proportions: Component A: 28.11 alicyclic epoxy resin, 14.05 xylene, 14.05 n-butanol, 14.55 organic-inorganic double-coated aluminum silver paste, 4.68 sericite, 18.74 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, and 0.05 defoaming agent.
[0077] The preparation method is as follows, S12. The mass ratio of graphene oxide to aluminum silver powder in the graphene oxide dispersion is 1:1500.
[0078] The rest is exactly the same as in Example 1.
[0079] The heat dissipation anticorrosive coatings of the above embodiments and comparative examples were tested according to GB / T 6748-2008 "Marine Antirust Paint Standard". Steel plates were used as substrates for the salt spray resistance and adhesion tests.
[0080] 1. Salt spray resistance test method: The test is carried out according to GB / T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes", using the salt spray corrosion test box HDYW-90 produced by Shanghai Hengding Instrument Factory.
[0081] 2. Adhesion test method: According to GB / T 5210-2006 "Standard for adhesion test of paint and varnish by pull-off method", the test was carried out using the HZ-1003B computer servo-type universal material testing machine produced by Dongguan Lixian Instrument Technology Co., Ltd.
[0082] UV resistance test method: Tested according to GB / T 14522-2008 "Artificial climate aging test method for plastics, coatings and rubber materials for mechanical industrial products - Fluorescent UV lamp", using the American Q-LAB UV aging test box and UV accelerated aging equipment with UVA-340 lamp.
[0083] Test method for heat dissipation effect: simulate a container, spray different heat dissipation coatings of the embodiments and comparative examples on 2m, 2m, and 3m iron sheets, and make them according to the same process. The thickness error of the paint film does not exceed 5μm. Assemble the iron sheets into a box of 2m wide × 2m high × 3m long, and place it outdoors in the summer when the sun is bright and the temperature is >35℃, in the same place, open and without shadows on each box, and place a thermometer of the same specification in the middle of the box 1m above the ground. Place it under high temperature for 3 hours and monitor the reading of the thermometer.
[0084] The test results are shown in the following table: Salt spray resistance Adhesion UV resistance Heat dissipation Example 1 12000h no rust, no blister, no crack, no fall off 10.74MPa No yellowing or powdering after 2000h 39±2℃ Example 2 10600h no rust, no blistering, no cracking, no falling off 9.71MPa No yellowing or powdering after 2000h 46±2℃ Example 3 11000h no rust, no blister, no crack, no fall off 9.16MPa No yellowing or powdering after 2000h 44±2℃ Example 4 10000h no rust, no blister, no crack, no fall off 8.96MPa No yellowing or powdering after 2000h 48±2℃ Example 5 11000h no rust, no blister, no crack, no fall off 9.54MPa No yellowing or powdering after 2000h 44±2℃ Example 6 11200h no rust, no blistering, no cracking, no falling off 9.98MPa No yellowing or powdering after 2000h 42±2℃ Comparative Example 1 No rust, blister, crack or fall off after 400h 10.55MPa No yellowing or powdering after 2000h 64±2℃ Comparative Example 2 12000h no rust, no blister, no crack, no fall off 10.16MPa Yellowing after 100 hours, powdering after 500 hours 40±2℃ Comparative Example 3 4800h without rust, blister, crack or fall off 9.92MPa No yellowing or powdering after 2000h 56±2℃ Comparative Example 4 12000h no rust, no blister, no crack, no fall off 4.94MPa No yellowing or powdering after 2000h 39±2℃ Comparative Example 5 8400h no rust, no blistering, no cracking, no falling off 9.24MPa No yellowing or powdering after 2000h 52±2℃ Comparative Example 6 9500h no rust, no blistering, no cracking, no falling off 9.81MPa No yellowing or powdering after 2000h 50±2℃ From the data comparison between Example 1 and Comparative Example 1, it can be seen that since Comparative Example 1 does not add organic-inorganic double-coated aluminum-silver paste, the salt spray resistance, that is, the anti-corrosion performance and heat dissipation performance of Comparative Example 1 are very poor.
[0085] From the data comparison of Example 1 and Comparative Example 2, it can be seen that since Comparative Example 2 only replaces the alicyclic epoxy resin with bisphenol A epoxy resin, although the salt spray resistance, adhesion and heat dissipation properties are not much different, the UV resistance becomes very poor.
[0086] From the data comparison between Example 1 and Comparative Example 3, it can be seen that due to the small addition ratio of the organic-inorganic double-coated aluminum-silver paste in Comparative Example 3, its salt spray resistance and heat dissipation are relatively poor.
[0087] From the data comparison between Example 1 and Comparative Example 4, it can be seen that due to the large addition ratio of the organic-inorganic double-coated aluminum-silver paste in Comparative Example 4, its adhesion is poor.
[0088] From the comparison of the data of Example 1 and Comparative Example 5, it can be seen that due to the excessive amount of graphene in Comparative Example 5, although the aluminum and silver are basically coated, the graphene-coated aluminum and silver powder contains more graphene than aluminum and silver, resulting in poor salt spray resistance and heat dissipation.
[0089] From the data comparison between Example 1 and Comparative Example 6, it can be seen that due to the excessive amount of aluminum-silver in Comparative Example 6, most of the aluminum-silver is not coated, resulting in poor salt spray resistance and heat dissipation.
[0090] This patent achieves the effect of mutual performance enhancement by optimizing alicyclic epoxy resin and graphene-coated aluminum silver, with excellent corrosion resistance and weather resistance, and can also achieve the effect of heat dissipation, solving the problem that container coatings in high-temperature sea areas are not durable and need frequent rework, and the high temperature inside the container has poor heat dissipation.
[0091] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A graphene-coated aluminum silver powder coating, characterized in that: It includes the following components and their weight parts: Component A: 26-33 epoxy resin, 13-17 xylene, 13-17 n-butanol, 13-17 organic-inorganic double-coated aluminum-silver paste, 4-6 sericite, 17-22 aluminum tripolyphosphate, 1 fumed silica, 0.1 leveling agent, 0.05 defoaming agent, the aluminum-silver paste of the organic-inorganic double-coated aluminum-silver paste is graphene-coated aluminum-silver paste, the graphene-coated aluminum-silver paste includes graphene-coated aluminum-silver powder, the leveling agent is a polyether-modified silicone leveling agent, and the defoaming agent is a polyether-modified silicone defoaming agent; Component B: 50 hexahydrophthalic anhydride, 2 anhydride accelerator, 24 xylene, 24 n-butanol.
2. The graphene-coated aluminum silver powder coating according to claim 1, characterized in that: The epoxy resin is an alicyclic epoxy resin.
3. A method for preparing the graphene-coated aluminum silver powder coating according to claim 1 or 2, characterized in that: The following steps are involved: S1. Preparation of graphene-coated aluminum silver powder: S11, adding the above-mentioned graphene oxide powder into deionized water, wherein the graphene oxide flake thickness is 1-10 nanometers and the diameter is 1-10 μm, and ultrasonic dispersion is performed for 30-120 minutes at an ultrasonic frequency of 50-100 KHz to obtain a graphene oxide dispersion liquid, wherein the concentration range of the graphene oxide dispersion liquid is 1-100 g / L; S12, adding the aluminum silver powder to the graphene oxide dispersion, wherein the particle size of the aluminum silver powder is in the range of 1 to 100 μm, and the mass ratio of graphene oxide to the aluminum silver powder in the graphene oxide dispersion is 1:100 to 1000; S13, using sulfuric acid or hydrochloric acid to adjust the pH of the graphene oxide dispersion, reacting at room temperature, using a stirring device to continuously stir during the reaction, the stirring speed range is 10-60r / min, and the pH range is 1-6; S14, after the reaction is complete, washing and filtering the obtained product, and drying it in an oven until it is completely dry to obtain graphene-coated aluminum silver powder; S2. Preparation of graphene-coated aluminum-silver paste: S21, taking 100 parts of the graphene-coated aluminum silver powder, 100 parts of D80 solvent oil, and 1 part of fatty acid, adding them into a ball mill and mixing and grinding for 5 hours to obtain a mixed slurry; S22, adding the mixed slurry to a vibrating screen with a mesh size of 250 meshes for filtering, and then adding the filtered mixed slurry to a filter press for pressing to obtain a graphene-coated aluminum-silver paste filter cake; S23, adding the graphene-coated aluminum-silver paste filter cake into a mixer and stirring evenly to obtain the graphene-coated aluminum-silver paste; S3, preparation of organic-inorganic double-coated aluminum-silver paste: S31, dispersing: dispersing the graphene-coated aluminum-silver paste in a mixed solvent of ethanol and water to obtain a uniform precursor; the volume ratio of the ethanol and water is 1:1, and the amount of the mixed solvent of ethanol and water added is 350% of the weight of the aluminum-silver paste; S32, inorganic coating: the above precursor is dripped into tetraethyl orthosilicate within 1 hour, and the mixture is stirred and heated while the temperature of the whole system is controlled at 60-70°C, and a hydrolysis reaction is carried out under the catalytic action of ammonia water. After completion, the mixture is cooled, washed and filtered to obtain an inorganic silica-coated / graphene-coated aluminum-silver paste; tetraethyl orthosilicate is used as a precursor of silica, and its addition amount is 40% of the weight of the aluminum-silver paste; the addition amount of ammonia water is 10% of the weight of the aluminum-silver paste; S33, organic coating: add toluene to a round-bottom flask equipped with a stirrer, a dropping funnel, and a reflux condenser, and disperse the inorganic silica-coated aluminum paste in toluene, wherein the amount of toluene added is 350% of the weight of the aluminum paste; then stir thoroughly for 30 minutes, and add silane coupling agent and azobisisobutyronitrile in sequence, wherein the amount of silane coupling agent added is 2% of the weight of the inorganic silica-coated aluminum paste, and the amount of azobisisobutyronitrile added is 1% of the weight of the inorganic silica-coated aluminum paste. 2%, evacuate the system and pass inert gas, repeat three times, and keep the whole reaction process under the protection of inert gas atmosphere, place the round-bottom flask in a water bath and heat it to 70°C, then add fluorine-containing acrylate monomer dropwise, the amount of fluorine-containing acrylate monomer added is 50% of the weight of inorganic silica-coated aluminum-silver paste; add dropwise in 1 hour; raise the system temperature to 85°C and continue to react for 4 hours, cool, wash and filter to obtain organic-inorganic double-coated aluminum-silver paste; S4. Preparation of graphene-coated aluminum silver powder coating: Preparation method of component A: Add the above xylene and n-butanol into a stirring tank, turn on the high-speed disperser, and rotate at a speed of 500-700 r / min for 1-10 min to obtain a uniformly mixed solvent; After adding the epoxy resin to the uniformly mixed solvent, the rotation speed is adjusted to 1500-2000 r / min, and heated at 50-100° C. until the alicyclic epoxy resin is completely dissolved to obtain a mixture A; The organic-inorganic double-coated aluminum-silver paste, sericite, aluminum tripolyphosphate and fumed silica are added to mixture A, dispersed at 1500-2000 r / min for 2-3 hours, and the fineness is tested by a scraper fineness meter to be less than 20 μm, to obtain mixture B; Adjust the speed to 800-1000r / min, add the above-mentioned leveling agent and defoaming agent to mixture B, stir for 10-15min, filter with 200-mesh filter cloth, and package; Preparation method of component B: Add the above-mentioned xylene, n-butanol, hexahydrophthalic anhydride and acid anhydride promoter into a stirring tank at a stirring speed of 800-1000 r / min. After the above-mentioned hexahydrophthalic anhydride and acid anhydride promoter are completely dissolved, filter with a 300-mesh filter and package.
4. The method for preparing a graphene-coated aluminum silver powder coating according to claim 3, characterized in that: The mass ratio of graphene oxide to aluminum silver powder in the graphene oxide dispersion in S12 is 1:500~800.
5. The method for preparing a graphene-coated aluminum silver powder coating according to claim 3, characterized in that: The pH value of S13 is in the range of 1 to 4.
6. A method for using the graphene-coated aluminum silver powder coating according to claim 1 or 2, characterized in that: The following steps are involved: Pretreatment: Pre-treat the metal surface by sandblasting, degreasing and rust removal, water washing, phosphating, passivation, deionized water washing, and drying of the phosphating film to remove oil and dust on the surface of the coated object; Spraying: Mix component A and component B in a ratio of 1:0.5 and spray on the workpiece; Curing: After spraying, let the workpiece dry in a 30℃ environment for 10-20 minutes, then cure the workpiece at 120-150℃ for 1 hour, and polish with 240-grit sandpaper.
7. The method for using the graphene-coated aluminum silver powder coating according to claim 3, characterized in that: After the curing step, a secondary spraying and curing step is added. Secondary spraying and curing: Follow the same spraying and curing steps as above to carry out secondary spraying and curing.
Citation Information
Patent Citations
Heavy duty anticorrosion graphene modified epoxy zinc-rich coating and preparation method thereof
CN109233565A
Prepartion method of environmental aluminum silver paste
CN101585087A
Heat-conductive and anti-corrosion coating based on graphene functional material and preparation method of same
CN104817930A
Method for industrially preparing graphene coated aluminum nanopowders
CN104923796A
Preparation method of fluoropolymer and silicon dioxide double-coated aluminum paste
CN107828251A